Empathetic Political Communication as the Political Identity of Female Legislators: A Phenomenological Study in the Surabaya City DPRD - Syam Maella, Nurannafi Farni; Farida, Farida; Njoto, Herlina Harsono; Sahharon, Hamizah; Amalia, Vinna (JURNAL KOMUNIKASI INDONESIA, 2026)
Politics has long been constructed as a masculine arena dominated by discourses of power, authority, and instrumental rationality. The presence of female legislators disrupts this hegemony by foregrounding empathetic modes of political communication that emphasize inclusivity, relational engagement, and responsiveness to social realities. These communicative practices not only contest dominant masculine norms in political discourse but also expand deliberative spaces and support the formulation of gender-responsive public policies. Accordingly, this study examines how female legislators in the Surabaya Legislative Council construct and enact empathetic political communication as a core expression of their political identity. Using a qualitative phenomenological approach, this research employed in-depth interviews and participant observation of eight female legislators from several commissions. The results of the study show that empathetic political communication is enacted through a dialogical and reflective communication approach characterized by emotional involvement, trust building, knowledge sharing, friendship, adaptation, demonstrating competence, and family harmony. These characteristics serve as strategies for navigating the male dominated political arena through three aspects: substantive readiness, women's representation, and soft power. Such communication practices not only provide female legislators with strategic advantages in a male dominated political arena but also contribute to reshaping the discourse of political leadership in Indonesia. This study offers practical implications for strengthening gender equality in legislative communication and provides a framework for integrating empathy into political discourse.